Prevalence and Occupational Risk Factors of Neck Pain among Desk Based Office Workers - Mehta, Pramod Kumar Singh; Yadav, Pooja (Journal of Nobel Medical College, 2025)
Background: Neck pain is a common work-related musculoskeletal disorder, especially for individuals with sedentary office jobs involving repetitive tasks. Poor posture and ergonomic issues increase stress on the cervical spine and muscles, impacting physical health, raising absenteeism, and reducing productivity. This study aims to investigate the prevalence, risk factors and consequences of neck pain in office workers. Materials and Methods: A cross-sectional survey of 179 participants from two organizations in Biratnagar, Nepal (98 from NMCTH and 81 from NTC) used self-administered questionnaires and convenient sampling to collect data. Results: Working more than 8 hours per day significantly increased the prevalence of neck pain to 78.9%, compared to 61.5% in those working 8 hours or less (p=0.030). Prolonged posture was reported by 74.5% of participants with neck pain, which significantly disrupted daily activities (100%), household chores (94.7%), and outdoor activities (100%) (p<0.001). Conclusion: Neck pain is very common among office workers in Biratnagar, mainly due to long work hours, heavy computer use, and poor posture. These factors seriously affect daily life and work performance. Improving workplace ergonomics and encouraging regular movement are key to reducing this problem.